Cytokine gene expression in intact anagen rat hair follicles - Little, J C; Westgate, G E; Evans, A; Granger, S P (Journal of investigative dermatology, 1994)
Substantial cellular proliferative activity is necessary to produce a mature hair follicle. Therefore, it is likely that cytokines and their receptors play an important controlling role. To provide an understanding of the mechanisms involved during hair growth, we investigated the expression of cytokines in rat anagen hair follicles. A new technique was developed that allowed the rapid isolation of large numbers of intact, viable, anagen, rat pelage hair follicles. Total RNA was isolated from these follicles using an acid-phenol-chloroform extraction and analyzed for cytokine expression. Using the conventional technique of Northern blotting, it was only possible to detect transcripts for transforming growth factor beta (TGF beta) and insulin-like growth factor I (IGFI). Polymerase chain reaction amplification of reverse-transcribed mRNA detected cDNA fragments for TGF beta, IGF I, IGF II, nerve growth factor beta (NGF beta), and interleukin-1 alpha (IL-1 alpha). The amplified products were confirmed by digestion with restriction endonucleases. The proteins themselves for TGF beta and IGF I have been shown to be present within the anagen hair follicle using immunogold antibody labeling. This study has provided the first reported cytokine expression profile of rat anagen hair follicles. It is likely that the analysis of the pattern and timing of expression of these cytokines in the follicle will provide valuable insights into hair growth regulation.